Enhancing mechanical strength of petung bamboo (dendrocalamus asper) composites using brackish water immersion - Benthony, Frans Robert; Suluh, Sallolo; Gusti, Chandra Sanima Adi; Ariyanto, Ariyanto (Jurnal Polimesin, 2025)
This study investigates and analyzes the effect of brackish water immersion on the mechanical properties of woven Petung bamboo (Dendrocalamus asper) reinforced epoxy composites. The bamboo, aged 5 years and 10 feet in length, was split, woven, and soaked in brackish water with varying salinity levels (10–30%) for 2, 4, 6, and 8 weeks. The composites were fabricated using epoxy resin and dried for two weeks before testing. Mechanical properties were evaluated through tensile and bending tests, following ASTM D3039 and ASTM C393 standards, respectively. The results show that immersion significantly improves mechanical strength under specific conditions. The highest tensile strength (74.75 MPa) was achieved by a 2-layer composite soaked for 2 weeks in 10% brackish water, while a 3-layer composite soaked for 4 weeks in 20% brackish water achieved the maximum bending strength of 84.73 MPa. Compared to untreated specimens, strength increases ranged from 30% to 60%, depending on the number of layers and immersion conditions. These findings suggest that brackish water immersion acts as an effective pre-treatment method, enhancing the fiber–matrix bonding and stiffness of bamboo composites. These results suggest that pre-treatment with brackish water can significantly enhance the mechanical performance of natural fiber composites, offering low-cost, sustainable composite materials applicable in construction, furniture, and eco-friendly product development.